DAMPAK KEBIJAKAN KEAMANAN LINGKUNGAN TIONGKOK TERHADAP KONDISI EKONOMI POLITIK MONGOLIA TAHUN 2013-2015 - Riski Ananda; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study explains about the impact of China's environmental security policy on Mongolia's political economy in 2013-2015. Mongolia is a rich country in mineral resources, especially coal. The biggest coal export partner for Mongolia is China. The economy of Mongolia is highly dependent on the value of China’s coal demand. China is experiencing serious environmental crisis problems so that the Chinese Government strives to make environmental issues its priority. The author obtains data from journals, books, articles, theses, reports, internet and online media to analyze this research. The theoretical framework that I use in this study is strukturalisme perspective, depedency theory from Theotonio Dos Santos, nation-state analysis unit and the concept of national interest by Nuchterlain. This research shows that environmental security policies in China are carried out by reducing imports and coal consumption in an effort to overcome environmental problems caused by coal in China. China also seeks to replace fossil energy sources by increasing the use of renewable energy such as wind, nuclear, water and geothermal energy. The impact of the implementation of this policy resulted in China reducing the value of coal  demand, which affected the political economy of Mongolia, which was heavily dependent on coal. Keywords: Policy, Environment, Coal, Economy, Politics, Export